2020
DOI: 10.1038/s41467-020-20190-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of dissociation in ketamine’s antidepressant effects

Abstract: Ketamine produces immediate antidepressant effects and has inspired research into next-generation treatments. Ketamine also has short term dissociative effects, in which individuals report altered consciousness and perceptions of themselves and their environment. However, whether ketamine’s dissociative side effects are necessary for its antidepressant effects remains unclear. This perspective examines the relationship between dissociative effects and acute and longer-lasting antidepressant response to ketamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 76 publications
2
64
0
6
Order By: Relevance
“…Our findings may have implications for the potential therapeutic use of ketamine. There are mixed findings and views as to whether dissociation is necessary to achieve antidepressant effects of ketamine [7, 8] or whether these effects are considered as adverse events. An answer may lie in the personalized responses of each individual person, which might require in-depth analysis of individual variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings may have implications for the potential therapeutic use of ketamine. There are mixed findings and views as to whether dissociation is necessary to achieve antidepressant effects of ketamine [7, 8] or whether these effects are considered as adverse events. An answer may lie in the personalized responses of each individual person, which might require in-depth analysis of individual variation.…”
Section: Discussionmentioning
confidence: 99%
“…There is mixed evidence as to whether dissociation is necessary for ketamine's antidepressant effect. For example, a meta-analysis showed it was not necessary [7], whereas another study demonstrated a correlation between reduction in depression scores and the depersonalization aspect of ketamine-induced dissociation in particular [8].…”
Section: Introductionmentioning
confidence: 99%
“…In fact it has been reported that dissociation could predict a robust and sustained antidepressant effect (Luckenbaugh et al, 2014;Niciu et al, 2018). However, one must consider that the latter correlation is debated (Ballard and Zarate, 2020) and that dissociative effects and sleep effects occur at different times (Vande Voort et al, 2017). Furthermore it is possible that ketamine may produce different effects in depressed and suicidal patients than in individuals without these conditions; in fact, ketamine can cause unpleasant dreams in healthy volunteers over the three post-administration nights (Blagrove et al, 2009) and has not decreased delirium in older adults undergoing negative experiences after major surgery (Avidan et al, 2017).…”
Section: Ketamine and Suicidal Behaviormentioning
confidence: 99%
“…Then proceed with inhibition of glutamatergic input to GABA interneurons and result in glutamatergic disinhibition resulting in decreased feedback and increased glutamatergic excitatory transmission. 5,6 Non-NMDA Mediators…”
Section: Nmda Receptors As Mediatorsmentioning
confidence: 99%
“…Another component involved in the antidepressant effect is the eukaryotic elongation factor 2 kinase (eEF2K), which is the key to mediating the effects of fast-acting antidepressants. 5,6,7 Potential mechanism of antidepressant of ketamine 2…”
Section: The Neurochemical Cascades and Other Mechanismsmentioning
confidence: 99%